What patient population is at greatest risk of having latent tuberculosis and require treatment?. Issue 11 (November 2015) - Hughes, Meghan; Lee, Jay H.
Abstract : Evidence‐Based Answer : The literature does not provide guidelines on when to start treatment for latent tuberculosis (TB). Foreignborn patients should be screened and treated for latent TB infection upon diagnosis to prevent the development of active TB infections, which are most likely to occur within 2 years of arrival to the United States (SOR: B, observation and epidemiologic trials).